2016
DOI: 10.1088/0953-8984/28/42/425701
|View full text |Cite
|
Sign up to set email alerts
|

SANS study of vortex lattice structural transition in optimally doped (Ba1−xKx)Fe2As2

Abstract: Abstract. Small-angle neutron scattering on high quality single crystalline Ba 1−x KxFe 2 As 2 reveals the transition from a low-field vortex solid phase with orientational order to a vortex polycrystal at high magnetic field. The vortex order-disorder transition is correlated with the second-peak feature in isothermal hysteresis loops, and is interpreted in terms of the generation of supplementary vortex solid dislocations. The sharp drop of the structure factor above the second peak field is explained by the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…However, as it can be seen in Fig. 3, there is no maximum in |m| at H = 30 kOe on the magnetic hysteresis curve registered at T = T cr = 21 K. Similarly, since the long-time relaxation measurements 25 and structural investigations using muon-spin rotation and small-angle neutron scattering experiments 47,48 showed that at the peak field H p the vortex system is completely disordered, the identification of the RST line with H p (T) is ruled out.…”
Section: Resultsmentioning
confidence: 79%
“…However, as it can be seen in Fig. 3, there is no maximum in |m| at H = 30 kOe on the magnetic hysteresis curve registered at T = T cr = 21 K. Similarly, since the long-time relaxation measurements 25 and structural investigations using muon-spin rotation and small-angle neutron scattering experiments 47,48 showed that at the peak field H p the vortex system is completely disordered, the identification of the RST line with H p (T) is ruled out.…”
Section: Resultsmentioning
confidence: 79%
“…An ordered vortex structure was observed in an area of 130 50 nm 2 in optimally doped Ba 0.6 K 0.4 Fe 2 As 2 by STM measurement [28]. With a large Ba 0.64 K 0.36 Fe 2 As 2 single crystal, SANS measurement observed Bragg peaks corresponding to a long-range ordered triangular lattice below H=0.75 T. With increasing magnetic field above 0.75 T, diffraction spots smeared and gave the characteristic pattern of circles from a polycrystalline structure, which was interpreted as a vortex order-disorder transition associated with the appearance of SMP in MHLs [29]. In optimally doped BaFe 2 (As 0.67 P 0.33 ) 2 single crystals, hexagonal VL was formed in the field range from 1 to 16 T revealed by SANS measurement, and no symmetry changes in the VL were observed [30].…”
mentioning
confidence: 99%
“…These results in Bi 2 Sr 2 CaCu 2 O 8+δ are consistent with SANS data in the pnictide material (Ba,K)Fe 2 As 2 . 36 Therefore, in this particular order-disorder transition no two-stage structural transformation is detected.…”
Section: Discussionmentioning
confidence: 87%
“…46 The fracturing of the vortex structure into large domains in the vortex glass phase could be a non-equilibrium feature, due to finite cooling rates during the nucleation of the structure in field-cooling experiments. 36 Nevertheless, the vortex glass presents non-hexatic order already inside the crystallites.…”
Section: Vortex Glass: Fracturing Into Large Non-hexatic Domainsmentioning
confidence: 99%
See 1 more Smart Citation